2015
DOI: 10.1016/j.jval.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Utility Based on the EuroQol Five-Dimensional Questionnaire in Patients with Chronic Heart Failure and Their Change Over Time: Results from the Swedish Heart Failure Registry

Abstract: Utilities in CHF and their change over time are influenced by diverse demographic and clinical factors. Our findings can be used to target clinical interventions and for economic evaluations of new therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
1
26
0
1
Order By: Relevance
“…The generic EQ‐5D domain scores and the VAS, which reflect patients' own assessment of their global health, while less specific to the aspects of health important to patients with HF, are also in line with the KCCQ results and extend assessment to the potential impact of vericiguat on broader aspects of HRQoL. Summary score improvements for the 5 and 10 mg arms were at a meaningful level (defined as 0.04 and 5 points for the US index score and the VAS, respectively) …”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The generic EQ‐5D domain scores and the VAS, which reflect patients' own assessment of their global health, while less specific to the aspects of health important to patients with HF, are also in line with the KCCQ results and extend assessment to the potential impact of vericiguat on broader aspects of HRQoL. Summary score improvements for the 5 and 10 mg arms were at a meaningful level (defined as 0.04 and 5 points for the US index score and the VAS, respectively) …”
Section: Discussionsupporting
confidence: 61%
“…The results of the exploratory patient‐reported endpoints in the SOCRATES‐PRESERVED trial, in the absence of changes in the primary endpoints, NT‐proBNP and LAV, generate the hypothesis of a potential clinically relevant improvement in patient health status in the higher dose arms of vericiguat. In key domains of the KCCQ and EQ‐5D, mean changes relative to placebo were above previously defined levels of MCID . At the level of individual patients, the responder analyses suggest as few as three to five patients need to be treated with the higher doses of vericiguat for one to feel moderately or substantially better.…”
Section: Discussionmentioning
confidence: 81%
“…However, the assumption of an annual decline in EQ-5D of 0.008 appears consistent with data from other studies; 1-year longitudinal data presented by Berg et al in patients with chronic HF suggests an annual decrease in EQ-5D of 0.006. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, higher EQ-5D US index scores were achieved after using of vericigaut and riociguat, which reflected the improved health of patients with HF. [ 25 , 26 ] Moreover, SOCRATES-PRESERVED trial reported higher doses of vericigaut (5 and 10 mg) mainly played the import role in increasing scores. But dose-dependent effects are not observed in the treatment of riociguat.…”
Section: Discussionmentioning
confidence: 99%